Rh particles in N-doped porous carbon materials derived from ZIF-8 as an efficient bifunctional electrocatalyst for the ORR and HER. Issue 23 (13th April 2021) - Sun, Can; Duan, Xinde; Song, Jiajun; Zhang, Mengxian; Jin, Yachao; Zhang, Mingdao; Song, Li; Cao, Hui
Abstract : ZIF-derived RhNC-900 bifunctional electrocatalysts for the oxygen reduction reaction and hydrogen evolution reaction have been prepared via a simple and scalable method, exhibiting excellent catalytic activity and promising performance. Abstract : Durable and efficient electrocatalysts toward the oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER) are crucial to the development of sustainable energy conversion. In this article, we report a highly active bifunctional electrocatalyst derived from ZIF-8 through simple heat-treatment activation. The resultant catalyst is enriched with Rh nanoparticles in the carbon matrix, showing excellent ORR performance with a half-wave potential ( E 1/2 ) of 0.803 V in alkaline electrolytes; it is simultaneously active for catalyzing the HER with an overpotential of 89 mV to reach a current density of 10 mA cm 2 in acidic electrolytes. The prepared RhNC-900 catalyst (1.47 wt% Rh) is comparable to the commercial Pt/C catalyst (20 wt% Pt) in terms of the ORR in alkaline media and might inspire new ideas for the development of fuel cells and water splitting.